Default Risk Premium and Aggregate Fluctuations in a Small Open Economy - S. Meral Çakıcı (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
This study investigates the implications of risk premium shocks for aggregate fluctuations in a small open economy with financial and informational frictions. A dynamic, stochastic, general equilibrium framework is developed, where the informational asymmetries among the agents in the model and the uncertainty in the production process necessitate financial intermediation in the economy. The Holmstrom-Tirole type of uncertainty in the production process also leads to collateralized borrowing by firms, with the physical capital stock of firms serving as the collateral as well as the factor of production. There is also a government sector in the economy that borrows domestically with a partial default risk. In order to compensate the lenders for the default risk included in the government bonds, the government has to offer them some risk premium in addition to the exogenously given world interest rate offered by the foreign bond issuers. It is shown that, under certain circumstances, it is possible for the government to reduce its debt and increase its spending in response to a positive, temporary risk premium shock.
Keywords: F41; G15; G21; H39; 330; default risk premium; dynamic stochastic general equilibrium; aggregate fluctuations; Risikoprämie; Schock; Bruttoinlandsprodukt; Asymmetrische Information; Allgemeines Gleichgewicht; Kleine offene Volkswirtschaft; Theorie